Motor Carrier Costs and Minimum Rate Regulation - Nicholson, Howard W. (Quarterly Journal of Economics, 1958)
I. California experience illustrates theoretical and practical difficulties of minimum rate regulation, 139. — II. Description of California's system of controlling minimum rates of intrastate carriers, 140. — III. Analysis of the effects of this policy, 144. — IV. Some fundamental objections to comprehensive systems of minimum rate control, 148.